Probiotic Potential of Indigenous (Bacillus sp. RCS1, Pantoea agglomerans RCS2, and Bacillus cereus strain RCS3) Isolated From Cobia Fish (Rachycentron canadum) and Their Antagonistic Effects on the Growth of Pathogenic Vibrio alginolyticus, Vibrio harveyi, Streptococcus iniae, and Streptococcus agalactiae - Amenyogbe, Eric; Huang, Jian-sheng; Chen, Gang; Wang, Wei-zheng (Frontiers in Marine Science, 2021)
Large-scale fish farming faces many environmental stresses, which affect their immune systems, growth performance, and physiological homeostasis, resulting in increase in their susceptibility to infections. Some of the most common bacterial infections of cobia fish (Rachycentron canadum) include streptococcosis, vibriosis, furunculosis and mycobacteriosis, and pastelleurosis. Probiotics could be helpful in reducing or limiting the incidence of severe disease infections or outbreaks. Therefore, the present study aimed to isolate the indigenous bacterial species from healthy cobia fish and then selected 3 strains, including Bacillus sp. RCS1 (MW560712), Pantoea agglomerans RCS2 (MW560713), and Bacillus cereus RCS3 (MW560714) from the gut of juvenile’s cobia having advantageous assets or positive characteristics. Their analysis indicated the presence of similar biochemical profiles and all could effectively utilize carbon sources. The biosafety assessment did not show any pathological symptoms after 10 days of injecting the fish with isolated bacteria. The results showed that all the isolated bacteria in the present study had low auto-aggregation capacity within the first 3 h of incubation. The isolated bacteria showed strong tolerance when exposed to a range of pH. Although asymmetrically, a slow rise in the growth of isolated bacteria was observed within the pH range of 1–8 for RC1, 1–7 for RC2, and 1–6 for RC3. The antagonistic effects of isolated bacterial strains on the development of pathogens, including Vibrio alginolyticus, Vibrio harveyi, Streptococcus iniae, and Streptococcus agalactiae, were investigated using Luria-Bertani (LB) agar plates. All the isolated bacteria exhibited inhibitory effects against the pathogens, including V. alginolyticus, V. harveyi, S. iniae, and S. agalactiae. These isolated bacteria were characterized with a wide range of antagonistic activities, non-hemolytic activities, high survivability after heat-treatments and safety confidence, and antibiotic susceptibility. Generally, the characteristics displayed by these strains indicated that they could be used as potential probiotics in the aquaculture industry.